Evaluating the effectiveness of social transfer policies on poverty for children with previous experience in poverty - Bárcena-Martín, Elena María; Blanco-Arana, María del Carmen; Pérez-Moreno, Salvador Jesús (Springer Nature, 2023)
This paper assesses the effectiveness of social benefit programs on children who had prior experience with poverty across 27 European countries in the years following the Great Recession (2012–2015). Even though social benefit functions might contribute to alleviating child poverty, our findings highlight that child poverty differs not only across social benefit functions, but also between children with and without previous experience in poverty. While living in a country with comparatively high family/children’s benefits is associated with lower child poverty risk, these benefits do not significantly prevent children from being poor when they have been in poverty in the past year. By contrast, old-age/survivor benefits appear to be strongly associated with a lower risk of poverty for children with previous experience in poverty. This is particularly noticeable in multigenerational households, especially in countries that provide limited support for families with children and allocate significant expenditure to pension benefits. This finding remains consistent even when using lower poverty thresholds.
Keywords: Economía; Pobreza; Social benefits; Child poverty; Prior experience in poverty; Family/children’s benefits; Old age/survivor benefits